Knowledge of Stroke Risk Factors and Warning Signs among the Residents of Majmaah, Saudi Arabia: A Cross-sectional Study - Bashayer Abdullah Al-Maymuni; Mohamed Sherif Sirajudeen (Journal of Clinical and Diagnostic Research)
Introduction: Stroke is a major cause of illness and death in Saudi Arabia and is considered a rapidly growing problem. Timely admission to a stroke care facility and control of stroke risk factors will enhance stroke treatment outcomes and prevention. Reducing the time between stroke onset and presentation to the hospital, as well as mitigating risk, depends on the knowledge of stroke patients, their family members and the general population. Aim: To assess the knowledge of stroke risk factors, warning signs and the level of physical activity of participants, as well as their associations with selected participant characteristics. Materials and Methods: This cross-sectional study was conducted in the rural community of Majmaah, Riyadh, Saudi Arabia. Data were collected using a web-based survey from 392 participants who were 18 years or older and able to read and write in Arabic. The validated questionnaire used in this survey consisted of three parts to determine demographics, knowledge of stroke warning signs, risk factors and physical activity. Binary logistic regression analysis was used to identify the associations between the knowledge components, the level of self-reported physical activity and selected participant characteristics. Adjusted Odds Ratios (OR) and their respective 95% Confidence Intervals (CIs) were calculated. Results: Among the 392 study participants, only 326 (83.2.16%) correctly identified the location of the stroke. Commonly recognised risk factors included stress in 287 (73.21%), smoking in 187 (47.7%) and hypertension in 167 (42.6%). The most frequently recognised symptoms were difficulty in speaking in 210 (53.57%), sudden severe headache in 172 (43.88%) and dizziness in 149 (38.01%). The most common correct response regarding what to do in the event of a stroke was to go to the hospital in 261 (66.58%). Among the participants, only 103 (26.28%) could correctly identify five or more risk factors and 213 (54.34%) could recognise three or more symptoms and warning signs. Conclusion: The majority of the study participants lacked knowledge about stroke risk factors. Nearly half of the participants were unable to recognise stroke symptoms and warning signs. Therefore, there is an urgent need to develop health education strategies to improve public awareness of stroke risk factors, warning signs and prevention among the population residing in rural areas of Saudi Arabia.